The Effect of Menstrual Cycle and Body Mass Index on The Risk of Polycystic Ovarian Syndrome (PCOS) in Adolescent Females in Tarakan City - Noviyanti, Nur Indah; Johan, Reza bintangdari; Ruqaiyah, Ruqaiyah (Pancasakti Journal Of Public Health Science And Research, 2024)
Polycystic Ovarian Syndrome (PCOS) is the most common gynecological issue among women of reproductive age, affecting ovarian function due to hormonal imbalances. The purpose of this study was to determine the effect of menstrual cycles and body mass index (BMI) on the risk of Polycystic Ovarian Syndrome (PCOS) in adolescent girls in Tarakan City. This research employed a quantitative approach with an observational analytic method and a cross-sectional study design. The sample consisted of 95 adolescent girls from SMA 2 Tarakan and was analyzed using univariate and bivariate analyses. The chi-square test revealed a p-value of 0.000, indicating a significant relationship between BMI, menstrual cycle, and the risk of PCOS in adolescent girls at SMA 2 Tarakan. Hormonal imbalances in adolescent girls can lead to the development of hirsutism due to increased hyperandrogenism. This condition is often accompanied by menstrual cycle irregularities and increased BMI, characterized by weight gain.